Low-dose, high-pitch, spiral (FLASH) mode versus conventional sequential method for coronary artery calcium scoring: A derivation-validation study - Niraj Nirmal Pandey; Sayannika Chakraborty; Mansi Verma; Priya Jagia (Journal of Cardiovascular and Thoracic Research)
Introduction: The present study sought to compare the diagnostic accuracy and radiation dose of ECG-gated, ultra-fast, low-dose, high-pitch, spiral (FLASH) mode versus conventional, ECG-gated, sequential coronary artery calcium (CAC) scoring in patients with suspected coronary artery disease (CAD). Methods: The study included 120 patients who underwent both conventional scanning and FLASH mode scanning and were subdivided into derivation and validation cohorts. In the conventional sequential (step-and-shoot) protocol, prospective ECG-gated, non-contrast acquisition was performed at 70% of R-R interval. The spiral (FLASH) mode utilized a high-pitch and high-speed gantry rotation scanning mode where acquisition of the entire heart was done within a single cardiac cycle with prospective ECG-gating at 70% of R-R interval. Results: Correlation between CAC scores derived from conventional (cCAC) and FLASH mode (fCAC) in derivation cohort was excellent (r=0.99; P<0.001). A linear regression model was used to develop a formula for deriving the estimated CAC score (eCAC) from fCAC (eCAC=0.978 x fCAC). In validation cohort, eCAC showed excellent agreement with cCAC (ICC=0.9983; 95%CI: 0.9972 - 0.9990). Excellent agreement for risk classification (weighted kappa=0.93898; 95%CI: 0.86833 - 1.0000) was observed with 95% (57/60) scores falling within the same risk category. Effective dose was significantly lower in FLASH mode (conventional, 0.58±0.21 mSv vs. FLASH, 0.34±0.12 mSv; P<0.0001). Conclusion: CAC scoring using FLASH mode is feasible with high accuracy and shows excellent agreement with conventional CAC scores at significantly reduced radiation doses.